Knockout of HIF-1α in tumor-associated macrophages enhances M2 polarization and attenuates their pro-angiogenic responses - Werno, Christian; Menrad, Heidi; Weigert, Andreas; Dehne, Nathalie; Goerdt, Sergij; Schledzewski, Kai; Kzhyshkowska, Julia; Brüne, Bernhard (Carcinogenesis, 2010)
Tumor-associated macrophages (TAMs) constitute major infiltrates of solid tumors and express a marker profile that characterizes alternatively activated macrophages (MФs). TAMs accumulate in hypoxic tumor regions, express high amounts of hypoxia-inducible factor-1 (HIF-1) and contribute to tumor angiogenesis and invasiveness. However, the precise role of HIF-1 on MФ infiltration and phenotype alterations remains poorly defined. Therefore, we cocultured wild type (wt) versus HIF-1α −/− MФs with tumor spheroids. Both, wt and HIF-1α −/− MФs, infiltrated hypoxic regions of tumor spheroids at equal rates and got alternatively activated. Interestingly, significantly higher amounts of HIF-1α −/− MФs expressed the TAM markers CD206 and stabilin-1 compared with wt phagocytes. Stimulation of infiltrated TAMs with lipopolysaccharide (LPS)/interferon-γ revealed a reduced expression of the pro-inflammatory markers interleukin (IL)-6, tumor necrosis factor-α and inducible nitric oxide synthase in HIF-1α −/− MФs. Furthermore, HIF-1α −/− MФs were less cytotoxic toward tumor cells. Although infiltration of MФs increased the invasive potential of tumor spheroids independently of HIF-1, the ability to stimulate differentiation of stem cells toward CD31-positive cells was triggered by wt but not by HIF-1α −/− MФs. Our data suggest that HIF-1α-deficient MФs develop a more prominent TAM marker profile accompanied by reduced cytotoxicity, whereas HIF-1 seems indispensable for the angiogenesis-promoting properties of TAMs.